Hidup Sehat, Bebas Kuman dengan Gerakan Mencuci Tangan pada Anak SDK Tes Desa Napan - Tangkonda, Elisabet; Weakalla, Eugenia Raflesia Anjali Yasinta (Universitas Nusa Cendana, 2024)
Health is the key to happiness in human life. Hand hygiene through the habit of washing hands is one of the effective steps to prevent the spread of germs. Elementary school children are the main population who are vulnerable to the spread of germs and diseases. The handwashing movement carried out at the Napan Village Test SDK aims to provide education on good and correct handwashing steps. Through this movement, children are given education about the importance of washing hands and are invited to know the proper steps to wash their hands. The activity result showed that the children were aware of the impact given through the movement of the habit of washing their hands regularly and correctly. Therefore, the role of teachers, parents, and adequate sanitation facilities in schools are also supporting factors for the success of this movement so that children become healthier and free from germs.